2022
DOI: 10.3390/horticulturae8090789
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Growth Regulators and Apical Bud Removal on Growth, Flowering, and Corms Production of Two Gladiolus Varieties

Abstract: Gladiolus is commonly propagated from corms. The multiplication rate of corms is low and to increase the propagation rate, we examined a combination of apical bud removal and the application of growth regulators. The experiments were conducted in two varieties, ‘Rose Supreme’ and ‘White Prosperity’, and over two seasons. The apical buds on the planting corms were either removed or left intact before the same corms were soaked in a suspension with either 100 ppm of benzyladenine (BA), 100 ppm of gibberellic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They also indicated that GA3 at 100 ppm helped produce the heaviest dry stems, and that GA3 at 300 ppm achieved the longest leaves. Elsadek et al, (2020) on Codiaeum Variegatum, Lima et al (2020) on Aloe vera, Hoque et al, (2021) on Gladiolus hybridus L, Khalafalla et al, (2022) on Gladiolus hybridus L. and Schriner and Klett (2022) on Lavandula angustifolia since they found that the foliar applications of gibberellins at a rate of 100 (ppm) caused an increase in vegetative growth parameters.…”
Section: Effect Of Planting Date Growth Stimulants Treatments and The...mentioning
confidence: 99%
“…They also indicated that GA3 at 100 ppm helped produce the heaviest dry stems, and that GA3 at 300 ppm achieved the longest leaves. Elsadek et al, (2020) on Codiaeum Variegatum, Lima et al (2020) on Aloe vera, Hoque et al, (2021) on Gladiolus hybridus L, Khalafalla et al, (2022) on Gladiolus hybridus L. and Schriner and Klett (2022) on Lavandula angustifolia since they found that the foliar applications of gibberellins at a rate of 100 (ppm) caused an increase in vegetative growth parameters.…”
Section: Effect Of Planting Date Growth Stimulants Treatments and The...mentioning
confidence: 99%